Princípios jurídicos na ciência do direito brasileiro contemporâneo: valores fundados na razão, normas de colmatação, mandamentos nucleares do sistema e mandamentos de otimização - Fernandes, Francis Ted (2015)
Determining what legal principals are is an arduous task. The uncertainty peculiar to signs, the ambiguity of the language and the decoding of this legal term, not always performed under scientific criteria, are the first obstacles to be overcome in this endeavor. One way to determine what legal principles are is to analyze their meaning and function according to the understanding of the main schools of legal thought: the school of natural law, positivism and post-positivism. For the school of natural law, principles are values arising from the human reason. Positivism basically presents two conceptions on principles: the first one does not address the issue, since the legal system would be complete, self-sufficient and non-evaluative. The second conception of the positivist school recognizes the principles as bridging standards, which could never be opposed to the law, intended to fill the gaps in the legal system. The vision of positivism on the principles shows that this school of thought sees the legal system as a closed one, whose validity foundation lies in its own standards, which, in turn, are founded on a fundamental standard, which is assumed and not expressed. For this line of thought, any content can be right, being unimportant to question the material morality or immorality of a legal text. The neutrality of positivism in face of the legal content of law has ended up involuntarily legitimizing some arbitrary and totalitarian regimes. The failure of positivism in responding to certain situations has demanded an evolution in legal thinking and codifications, which propitiated an opening of the legal system to values and the consideration of content of what is right. In this new chapter of history, arises the post-positivist thought, which admits the principles as positivized values in the system, true standards that can solve concrete cases, as long as applied with an appropriate methodology. In addition to the standards, applicable to the greatest extent possible, the principles are considered as nuclear commandments of the legal system, which structures this system, granting unity to it, and, also, acting as vectors of interpretation of legal rules. Currently, in Brazil, the principles are also designed as bridging standards by virtue of the application of article 4 of the Law of Introduction to the Standards in Brazilian Law, since they were designed for the positivist school. There are several deviations on the application of legal principles, such as practices consisting in moving away the application of rules to certain concrete cases, under the guise of providing a solution based on principles, an effective expedient without a cohesive method and without justification supported by a solid argumentative process. This practice represents a risk to the typical activity of the Legislative Branch. It is assumed that the interpretation of the law and the resolution of concrete cases based on principles broadens the sphere of indeterminacy to which the interpreter is subjected, but this indeterminacy must be admitted, with a view to achieving the implicit justice claim in the legal system